Chemical fractionation of arsenic and heavy metals in fine particle matter and its implications for risk assessment: A case study in Nanjing, China. (February 2015) - Li, Huiming; Wang, Jinhua; Wang, Qin'geng; Qian, Xin; Qian, Yu; Yang, Meng; Li, Fengying; Lu, Hao; Wang, Cheng
Abstract: A four-step sequential extraction procedure was used to study the chemical fractionation of As and heavy metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn) in fine particulate matter (PM2.5 ) collected from Nanjing, China. The mass concentrations of most PM2.5 samples exceeded the 24 h standard (75 μg/m 3 ) recommended by the new national ambient air quality standard of China. The most abundant elements were Fe, Zn and Pb, while As and Cd were present at the lowest concentrations. As, Cd, Cu, Mn, Pb and Zn were mostly present in the two mobile fractions, including the soluble and exchangeable fraction (F1), and carbonates, oxides and reducible fraction (F2). Fe had the highest proportion present in the residual fraction (F4). Relatively high proportions of the metals Ni and Cr were present in the oxidizable and sulfidic fraction (F3). High proportions of Zn, As and Cu and lower proportions of Cd, Cr and Fe were present in the potentially mobile phases. The enrichment factor, contamination factor and risk assessment code were calculated to analyze the main sources and assess the environmental risks of the metals in PM2.5 . The carcinogenic risks of As, Cd, Ni and Pb were all lower than the accepted criterion of 10 −6, whereas the carcinogenic risks of Cr for children and As and Cr for adults were higher than 10 −6 . The non-carcinogenic health risk of As and heavy metals because of PM2.5 exposure for children and adults were lower than but close to the safe level of 1. Highlights: The fractionation distribution pattern and mobility differed among metals in PM2.5 . Zn, As, Cd, Cu, and Ni showed high environmental risk and Pb showed a medium risk. Human carcinogenic risk from metals in PM2.5 was higher than accepted criterion. The non-carcinogenic human health risk was lower than but close to the safe level.